Letalidade feminina, feminismo e polícia militar: análise de crimes de feminicídio e de homicídio de pessoas do sexo feminino na cidade de fortaleza(2015-2019) - Loureiro, Ythalo Frota (2022)
The research intends to investigate the relationship between female lethality, feminism, and military police. It is hypothesized that the microsystem of protection for women victims of violence depends on the work of the military at a crime scene and on the resistance of conservatism to the advancement of the agenda of rights historically claimed by the feminist movement. As a methodology, in addition to the bibliography on conservatism, black feminism, femicide and the Brazilian military police, an intersectional approach is used in the analysis of 289 police inquiries and judicial proceedings of the Courts of the District of Fortaleza, related to homicide crimes of women and femicides that occurred between 2015 and 2019. In empirical research, the race/color of the victims, the social status of the crime scene, the contexts, instruments, and narratives of military personnel are considered in the initial stage of the criminal investigation. As a result, the invisibility of markers of race/color of victims, gender and social status of crime scenes was verified in official statistics, made available to the public through the internet. Analyzing the expert reports, it was found that most victims of female homicides and femicides are women classified as “ pardas (a kind of black race) (74.83% of the sampling ) and that female lethality is concentrated in areas classified as “ Poor Neighborhood Suburb ” (93 42% of pro c edures and 86.46% of neighborhoods in Fortaleza). It was also found that the violent and intentional deaths of women are not limited to the context of “femicide” (14%), so that the violent death of women is still present in the contexts of “ drug trafficki n g” (30%) and in “other” circumstances and motivations (10%). 47% of the procedures did not have the circumstances or motives revealed, indicating a high rate of crimes without clear authorship, and underreporting of femicides. Moderate feminist theories ( Silvia Federici and Bell hooks) can explain sexist exploitation and oppression against black and racialized women. In the legislative process, which resulted in the creation of femicide, the conservative sector resisted the permanence of the term “gender”, which appeared in the original project. It was also found that the discourse of military police officers corresponds to the ideals proposed by conservatism, which reduces femicide to a "crime of passion", reverberating the sexist version of the aggressors and giving little or no importance to lethal crime from a gender perspective.